2004
DOI: 10.1111/j.1365-3040.2004.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption during leaf nitrate assimilation in a C3 and C4 plant: the role of mitochondrial respiration

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
(29 reference statements)
1
21
0
1
Order By: Relevance
“…A number of experimental studies (Searles and Bloom, 2003;Cousins and Bloom, 2004;Rachmilevitch et al, 2004) showed that the AQ was about 0.1 higher for growth on NH 3 compared with NO 3 in ambient atmospheric conditions for wheat, maize, tomato (Solanum lycopersicum), and Arabidopsis, in agreement with our calculation for rice. However, the lower AQ for NO 3 was not seen under conditions where photorespiration was suppressed, such as elevated CO 2 or reduced O 2 , and NO 3 assimilation was reduced.…”
Section: Quantum Demand and Photosynthetic Yieldsupporting
confidence: 80%
“…A number of experimental studies (Searles and Bloom, 2003;Cousins and Bloom, 2004;Rachmilevitch et al, 2004) showed that the AQ was about 0.1 higher for growth on NH 3 compared with NO 3 in ambient atmospheric conditions for wheat, maize, tomato (Solanum lycopersicum), and Arabidopsis, in agreement with our calculation for rice. However, the lower AQ for NO 3 was not seen under conditions where photorespiration was suppressed, such as elevated CO 2 or reduced O 2 , and NO 3 assimilation was reduced.…”
Section: Quantum Demand and Photosynthetic Yieldsupporting
confidence: 80%
“…4). Assimilation of NO 3 2 expends about 25% of carbon catabolism, whereas that of NH 4 + expends about 3% (Bloom et al, 1992;Cousins and Bloom, 2004). Therefore, it is expected that CO 2 inhibition of NO 3 2 assimilation would produce observable changes in respiratory gas fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the hypothesis that $NO_{3}^{-}$ assimilation in C 3 plants depends on photorespiration . By contrast, shoot $\hbox{NO}_{3}^{-}$ assimilation in C 4 plants proves relatively insensitive to CO 2 levels (maize,12, 27 Flaveria bidentis and Amaranthus retroflexus (Bloom AJ, unpublished)). Therefore photorespiration and the C 4 pathway appear to have a previously unrecognised function: they shuttle chemical energy between organelles to convert $\hbox{NO}_{3}^{-}$ into amino acids.…”
Section: The Discoverymentioning
confidence: 99%
“…We recently discovered a key interaction between biochemical pathways in plants for carbon metabolism and conversion of inorganic nitrogen into amino acids 9–12. This interaction may account for much of the variation in plant responses to elevated CO 2 concentrations.…”
mentioning
confidence: 99%